INFLUENCE OF DISORDER ON THE STATISTICS OF SEPARATION OF ELECTRONIC LEVELS OF NANOPARTICLES CU3568 - Medrano, L. (2009)
In the present work we study the influence of disorder on the electronic level statistics of a copper nanoparticle with 3568 atoms (Cu3568). The most stable configuration was obtained from molecular dynamic simulations employing a Johnson’s potential for copper. The results indicate that for weak disorder on the on-site energy of the tight-binding Hamiltonian, the nearest-neighbors level spacing distribution is similar to the Wigner distribution. Howerver, for strong disorder the distribution changes to a Poisson-like distribution which is expected for strongly disordered systems.